2019
DOI: 10.1002/brb3.1315
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic changes and therapeutic drug monitoring of lamotrigine during pregnancy

Abstract: Objectives To evaluate the pharmacokinetic changes in lamotrigine (LTG) from prepregnancy to postpartum and to assess the impact of therapeutic drug monitoring (TDM) on seizure management during pregnancy in a Chinese population. Methods A series of women who were on LTG monotherapy before conception or during pregnancy were included in this retrospective study. The clinical characteristics of the mothers and fetuses were collected. The apparent clearance (AC) and the ratio to target concentration (RTC) were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
57
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(60 citation statements)
references
References 22 publications
2
57
0
1
Order By: Relevance
“…A noticeable pharmacokinetic change in LTG during pregnancy is attributed to estrogen‐induced glucuronidation and increased renal blood flow, 13 making it challenging to stabilize plasma levels during pregnancy 14 . Previous studies have shown that apparent oral clearance of LTG in the second trimester and third trimester almost doubled, and total blood drug concentration decreased by 40%–60%, compared to that of the nonpregnant baseline 10,15 . In this study, the maximal clearance of LTG increased by 3.42 times, and the mean blood drug levels decreased by 57% in the second trimester (Figures 2 and 3).…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…A noticeable pharmacokinetic change in LTG during pregnancy is attributed to estrogen‐induced glucuronidation and increased renal blood flow, 13 making it challenging to stabilize plasma levels during pregnancy 14 . Previous studies have shown that apparent oral clearance of LTG in the second trimester and third trimester almost doubled, and total blood drug concentration decreased by 40%–60%, compared to that of the nonpregnant baseline 10,15 . In this study, the maximal clearance of LTG increased by 3.42 times, and the mean blood drug levels decreased by 57% in the second trimester (Figures 2 and 3).…”
Section: Discussionmentioning
confidence: 56%
“…Pennell et al recommended monthly monitoring of AED levels during pregnancy, with the possible exception of carbamazepine (CBZ) due to the clearance and dose being virtually unchanged 3 . Some studies suggested a dosage adjustment if an AED level decreased by 15%–25% that of the nonpregnant target concentration, especially for pregnancies with risk factors of convulsions 9,10 . Currently, available data on pharmacokinetics changes correlated with pregnancy and dosage adjustments guided by TDM for newer AEDs are insufficient, especially for LEV and OXC.…”
Section: Introductionmentioning
confidence: 99%
“…This is probably because the older South African national treatment guidelines recommended VPA and lamotrigine as first-line treatments for epilepsy and mood disorders in women receiving ART, driven by concerns of pharmacokinetic interactions between AEDs and antiretroviral agents (including dolutegravir, which has recently been introduced as part of first-line HIV treatment in South Africa) [ 20 , 34 ]. Although lamotrigine is the other recommended agent for WOCBA and pregnant women, the complicated initiation regimen, the need for intensive therapeutic drug monitoring particularly during the pregnancy and after delivery [ 35 ], and concerns regarding the risk of severe skin reactions, has contributed to the preferential prescribing of VPA in this population. Only 9% of women who experienced a pregnancy in that year and who were taking any type of AED/MSM were exposed to lamotrigine, compared with 45–47% who were exposed to VPA (Table 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…The metabolization of lamotrigine occurs in the liver and the enzymes responsible for this process are induced by pregnancy (69). So, lamotrigine clearance increases progressively and in order to maintain a therapeutic drug concentration, a dose increase is required (70). This change of the dose should be guided by clinical response.…”
Section: Mood Stabilizersmentioning
confidence: 99%